Quantum polarization tomography of bright squeezed light - Müller, C. R.; Stoklasa, B.; Peuntinger, C.; Gabriel, C.; Rehácek, J.; Hradil, Z.; Klimov, A. B.; Leuchs, Gerd; Marquardt, Christoph; Sánchez-Soto, L. L. (Frontiers in Optics, FIO 2012, 2012)
We reconstruct the polarization sector of a bright polarization squeezed beam starting from a complete set of Stokes measurements. We use both the inverse Radon transformation and a novel maximum likelihood algorithm. We find that the maximum likelihood reconstruction provides significantly higher statistical inversion stability, which allows us to get reconstructions of the same quality but from far smaller data sets. © OSA 2012.
CRIS-Team Scopus Importer:2022-06-05